Navigating against the surge of Salafism in Indonesia’s Malay society - Zulkifli Zulkifli (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2026)
As a global movement, Salafism has transformed the religious landscape of the Malay world, which is commonly associated with moderate religious characteristics. While some scholars have found Malay acceptance of Salafi ideology in Southeast Asia, this article explains Salafi activism in Bangka Belitung and the resistance of traditional religious authorities to it. The paper utilises a qualitative approach, combining library studies of online and offline sources with field research through interviews. A comparative social movement perspective, particularly political opportunity structure and resource mobilisation, was used to gain a holistic comprehension of the topic. The study found that Salafi activism gained momentum with the establishment of Bangka Belitung as a new province and the changing structure of society, which provided room for Salafi activists to mobilise resources in da‘wah (proselytisation) and education. To promote their ideology, recruit followers, and exert influence on Malay society, they conducted various activities, including religious gathering forums and learning circles known as halaqah and dawrah in mosques, the establishment of Islamic schools and pesantren, publication, and the use of communication and information technology. Although it remains small and exclusive, Salafi activism has confronted traditional religious authorities that tend to have a passive, tolerant attitude towards it. In general, they applied two main approaches: a preventive approach against Salafi ideological influence and a defensive approach to protect the internal Malay Muslim community, including strategic actions to avoid internal religious conflicts and maintain peace and harmony in the plural society.